2005
DOI: 10.1099/vir.0.81352-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the avian pneumovirus conserved transcriptional gene start sequence identifying critical residues

Abstract: Seven of the eight genes in the avian pneumovirus (APV) genome contain a conserved 9 nt transcriptional start sequence with the virus large (L) polymerase gene differing from the consensus at three positions. The sequence requirements of the APV transcriptional gene start sequence were investigated by generating a series of mutations in which each of the nine conserved bases was mutated to each of the other three possible nucleotides in a minigenome containing two reporter genes. The effect of each mutation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…A previously comprehensive minigenome investigation of gene start signal efficiencies showed that the CCCUGUUCA was most efficient and that the variant sequence of CCCCGUUCA found on subtype B SH and G proteins would be expected to reduce transcription of those genes (Edworthy & Easton, 2005). The L gene transcription start sequences proved an exception and minigenome studies showed a reduced transcription efficiency (Edworthy & Easton, 2005), as might be expected for a gene coding a protein needed in smaller amounts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previously comprehensive minigenome investigation of gene start signal efficiencies showed that the CCCUGUUCA was most efficient and that the variant sequence of CCCCGUUCA found on subtype B SH and G proteins would be expected to reduce transcription of those genes (Edworthy & Easton, 2005). The L gene transcription start sequences proved an exception and minigenome studies showed a reduced transcription efficiency (Edworthy & Easton, 2005), as might be expected for a gene coding a protein needed in smaller amounts.…”
Section: Discussionmentioning
confidence: 99%
“…The L gene transcription start sequences proved an exception and minigenome studies showed a reduced transcription efficiency (Edworthy & Easton, 2005), as might be expected for a gene coding a protein needed in smaller amounts. Surprisingly gene starts of the otherwise more distantly related subtype C viruses (Brown et al, 2014) like the subtype A viruses all used CCCUGUUCA, but again with the exception of the L gene.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the PVM GS has one of five possible sequences (Table 1), the consensus sequence being AGGAyAArT, suggesting the possibility of differential expression of genes or a tolerance of variation in GS sequence (Chambers et al, 1990a;Chambers et al, 1990b). The GS sequences of both APV and RSV have been subjected to mutational analysis that identified residues important for the initiation of transcription (Edworthy and Easton, 2005;Kuo et al, 1997). Here, we describe a similar analysis of the role of each of the nine individual bases of the PVM GS sequence using a reverse genetics approach.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the efficiency of initiation of transcription by different mutants of the PVM GS signal a dicistronic minigenome was constructed (Figure 1), containing two genes, similar to those described previously for APV and RSV (Edworthy and Easton, 2005;Kuo et al, 1996). The first gene in the PVM minigenome encoded bacterial chloramphenicol acetyl transferase (CAT) and was flanked by the N gene GS signal (AGGATAAAT) and the L gene GE signal (TAGTTAACAAAAAA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation